Developing locally relevant outreach programs for same sex attracted youth in regional areas - Lobo, Roanna; Brown, Graham; Edwards, J. (Australian Health Promotion Association, 2007)
Issue addressed: This paper reports on the process evaluation of the Same Sky project,1 which was aimed at developing regional community support programs for same sex attracted youth (SSAY) and their families in four regional sites in Western Australia. A multi-faceted approach modelled on successful urban outreach programs was used to build professional capacity and develop peer-based support programs in the community. Methods: A triangulated mixed methods evaluation design was implemented to capture various outputs and outcomes of the intervention strategies. Data were collected via interviews and questionnaires and by assessing community readiness through community participation and involvement in the programs and through demand for printed resources.Results: There was increased community awareness of same sex attraction issues and professional capacity to help SSAY regionally following training and distribution of printed resources. Improved alliances between regional and metropolitan service providers were also evident. Not all of the planned peer support interventions could be implemented. Drop-in centres and peer support groups proved particularly problematic to establish. Basing the project officer in one of the rural sites was notable in improving project progress. Conclusions: Some aspects of the urban outreach models for SSAY were transportable to rural areas, others were not. Some specific problems identified were a lack of community readiness, a distrust of ‘outsiders’ to the community, significant differences between the needs of SSAY across regional demonstration sites, and difficulties in engaging locally based volunteers and agencies to develop and run rural outreach services.